American Constitutional Law : The Bill of Rights and Subsequent Amendments - Rossum, Ralph A. (Polity Press, 2007)
This book is designed as a basic text for courses in constitutional law and civil liberties. As with the previous editions, its approach to these subjects is based on three major premises. First, the study of the Constitution and constitutional law is of fundamental importance to a full and coherent understanding of principles, prospects,and problems of America's democratic republic.Cases should be examined not merely to foster an appreciation of what court majorities have thoughgt of particular issues at certain points in time ( although that is obviously important ) , but also to gain a deeper and fuller understanding of the principles at the very heart of the American constitutional system.